Counseling as a Catalyst for Psychological Freedom and Self-Potential - Utami Niki Kusaini; Rema Syelvita; Berru Amalianita; Zubaidah; Yulianti (Outline Publisher, 2025)
This article reviews the role of counseling as a means to help individuals develop their potential in order to achieve psychological freedom. With a systematic approach, counseling helps individuals explore their strengths and weaknesses, and formulate life goals that they want to achieve. This process is not only oriented towards solving psychological problems, but also supports continuous self-development, which can ultimately strengthen self-confidence, increase motivation, and improve individuals' abilities in facing various life challenges. Thus, counseling has a significant role in supporting individuals to live more meaningful and satisfying lives, and achieve the desired psychological well-being. Research and theory that underlie counseling practice show that this approach can have a significant positive influence on an individual's mental well-being.